MEMES AS CULTURAL TEXTS: COLLECTIVE IDENTITY AND IDEOLOGY IN VISUAL DISCOURSE (KONFERENSIYA, 2025)
This article examines memes as cultural texts embedded in thesocial, political, and ideological dynamics of digital communication. Moving beyondtheir humorous surface, memes are positioned as semiotic artifacts that performidentity work, negotiate cultural power, and structure collective meaning-makingwithin online communities. By drawing on multimodal discourse analysis,ethnography of communication, and cultural theory, the study analyzes memes asinstruments of symbolic representation, ideological reproduction, and digital folkcreativity. It highlights how visual discourse enables communities to co-createcultural narratives, contest dominant ideologies, and sustain evolving digital identitiesthrough shared symbols and visual metaphors